Large rupture strain cotton ropes hybridized with affordable fiberglass chopped strand mat sheets for enhanced compressive behavior of reinforced concrete columns - Saingam, Panumas; Gadagamma, Chaitanya Krishna; Hussain, Qudeer; Ejaz, Ali; Hlaing, Hnin Hnin; Suwannatrai, Rawirot; Khan, Kaffayatullah; Suparp, Suniti (My University, 2024)
The hybrid confinement system combines various fiber types within a single matrix, allowing for the adjustment of volumetric ratios to optimize confinement performance. Synthetic FRPs are more expensive and have a higher carbon footprint due to significant CO2 emissions during production. In response, this study presents an innovative hybrid confinement approach using two natural materials: cotton ropes and FSMS (CFS) to improve concrete strength and ductility. Specimens, standardized at 300 mm height and 150 mm diameter with longitudinal steel bars and stirrups, were divided into two groups based on CFS configurations. The stress-strain response of CFS-confined concrete displayed distinctive behavior: an initial parabolic phase leading to peak compressive stress (ultimate strength), followed by a linearly degrading phase. Across all subgroups, CFS confinement significantly enhanced ultimate strength and corresponding compressive strains, with Subgroup 2A achieving the highest improvements of 246 % in ultimate strength and 1477 % in strain. Moreover, the ductility gain was reported as high as 20 for CFS-confined concrete. A non-proportional enhancement in the compressive behavior was observed with the increase in confinement ratio. Predictive models were developed for the idealized two-branch response of CFS-confined concrete, encompassing expressions based on nonlinear regression for ultimate strength, corresponding strain, ultimate strain, and elastic modulus. Two existing models were modified to trach each branch of the response. Integrating these two adjusted models closely replicated the experimental compressive curves.
Keywords: Compression; Concrete; Confinement; Hybrid; Regression